International energy technology transfers for climate change mitigation: what, who, how, why, when, where, how much and the implications for international institutional architecture - Thomas L. Brewer (Center for Economic Studies and ifo Institute (CESifo), 2008)
The goal of the paper is to expand and refine the international technology transfer negotiating and analytic agendas and to reframe the issues. The paper presents concepts, indicators, illustrations and data that identify and measure international transfers of energy technologies that can be used to mitigate climate change. Among the questions on that agenda are how much technology transfer there has been to date, and how much will be needed in the future, especially to assist non-Annex I developing countries in their efforts to mitigate climate change. Before the how much questions can be answered, however, there are several prior questions, and hence the many other elements of the subtitle of the paper: what, who, how, why, when, where. These aspects of international technology transfer vary significantly among three existing institutional settings and among the associated analytic paradigms: North-South Official Development Assistance, Global Private International Investment and Trade, and International Public-Private Cooperation Agreements. The principal sections of the paper focus on features of international technology transfers in these institutional settings and on illustrations drawn from the biodiesel industry, especially the use of jatropha tree as the source of the feedstock. The conclusions are summarized as follows: (i) Technologies include intangible know-how and services, as well as tangible goods in the form of production process equipment and finished products. (ii) International transfers of some types of technology are much easier to measure than others. (iii) International technology transfers are highly industry-specific. (iv) Even for individual industries, it is necessary to use multiple indicators of technology transfers. (v) Patterns in the types of technology and methods of transfer vary across the three institutional settings examined in the paper. (vi) All three of the institutional arrangements are probably under-performing and inadequa.
Keywords: F18; F23; F59; 330; Technologietransfer; Energietechnik; Klimaschutz; Institutionalismus; Nord-Süd-Beziehungen; Welt